Synergistic regulation and optimization of microstructure, coercivity, and thermal stability in sintered NdFeB magnets through grain boundary diffusion of Dy and Al elements - Rui Chang; Guangzhu Bai; Yaping Li; Zhi Yan; Xiufang Qin; Jingdong Guo; Fang Wang; Xiaohong Xu (Journal of Materials Research and Technology)
The grain boundary diffusion process (GBDP) is a well-established method for producing high-performance NdFeB magnets. However, the limited diffusion ability of heavy rare earth (HRE) elements, which are only attached to the surface of the magnet, has been a major concern in the industry. In this study, we utilize the GBDP method to diffuse low-melting-point DyAl alloy into magnets, resulting in the formation of continuous Dy-, Al-, and Nd-rich thin grain boundary phases and (Nd,Dy)2Fe14B shells with diffusion depths over 1500 μm. These results suggest that the presence of continuous Dy-, Al-, and Nd-rich thin grain boundary phases is crucial in promoting the diffusion of Dy elements in magnets. Furthermore, these thin and continuous grain boundary phases effectively isolate the Nd2Fe14B grains, preventing the simultaneous reversal of adjacent grains. As a result, the coercivity of the N42-DyAl magnet increases from 12.07 kOe to 19.95 kOe at room temperature and from 5.17 kOe to 10.76 kOe at high temperature (120 °C). The N42-DyAl magnets also exhibit a large coercivity temperature coefficient of −0.485%/°C and excellent thermal stability. This optimized effect of synergistic multi-element grain boundary diffusion creates an extensive core-shell structure, enhancing the anisotropy field and increasing the coercivity.